Discovery of natural products with metal-binding properties as promising antibacterial agents. (3rd June 2019) - Dandawate, Prasad; Padhye, Subhash; Schobert, Rainer; Biersack, Bernhard
ABSTRACT: Introduction : More than 50% of the clinically established antibiotics are either genuine natural products or derivatives thereof, featuring a mode of action decisively depending on their metal affinity and suitability as metal complex ligands. As their structural diversity and harvest from renewable sources is well-nigh inexhaustible, any future quest for affordable new antibiotics will have to concentrate on natural drugs with obvious metal ligating properties. Areas covered : The authors provide an overview of the promising developments in the field of antibiotic natural products with metal-binding properties with a specific focus on metal binders such as polyphenols, quinones, 3-acyltetramic and -tetronic acids. Works published by the authors are discussed in this manuscript as well as articles derived from PubMed and Scifinder. Expert opinion : Natural products with metal-binding properties possess a great potential for the development of drugs against various bacteria. There are many derivatives with great potential against multidrug-resistant bacteria as well. Synthetic approaches to structurally complex and/or rare natural products have added significantly to the cracking of synthetic problems. Thus, this field of scientific research appears attractive both to chemists and to clinicians.